Materials for biomedical engineering : nanobiomaterials in tissue engineering - Holban, Alina Maria; Grumezescu, Alexandru Mihai (Elsevier, 2019)
Materials for Biomedical Engineering: Nanobiomaterials in Tissue Engineering highlights the impact of novel bioactive materials in both current applications and their potential in the future progress of tissue engineering and regenerative medicine. Tissue engineering is a well investigated and challenging bio-medical field, with promising perspectives to improve and support the quality of life in diseased patients. This book brings together the latest research findings regarding the design and versatility of bioactive materials and their potential in tissue engineering. In addition, recent progress in soft and hard tissue engineering is presented within the chapters of the book.